Altered Temporal Variations of Functional Connectivity Associated With Surgical Outcomes in Drug-Resistant Temporal Lobe Epilepsy - Guo, Danni; Feng, Li; Yang, Zhiquan; Li, Rong; Xiao, Bo; Wen, Shirui; Du, Yangsa; Deng, Chijun; Wang, Xuyang; Liu, Dingyang; Xie, Fangfang (Frontiers in Neuroscience, 2022)
Background: Currently, more than one-third of drug-resistant temporal lobe epilepsy (TLE) patients continued to develop seizures after resection surgery. Dynamic functional network connectivity (DFNC) analyses, capturing temporal properties of functional connectivity during MRI acquisition, may help us to identify unfavorable surgical outcomes. The purpose of this work was to explore the association of DFNC variations of preoperative resting-state MRI and surgical outcomes in patients with drug-resistant TLE. Methods: We evaluated 61 TLE patients matched for age and gender with 51 healthy controls (HC). TLE patients were classiﬁed with seizure-free (n=39) and not seizure-free (n=16) based on the Engel surgical outcome scale. Six patients were unable to confirm the postoperative status and were not included in subgroups analysis. The DFNC was calculated using group spatial independent component analysis and sliding window approach. Results: DFNC analyses suggested two distinct connectivity ‘States’. The dynamic connectivity state of TLE patients were different from HC. TLE subgroups analyses showed not seizure-free (NSF) patients spent significantly more time in State II, compared to seizure-free (SF) patients and HC. Further, number of transitions from State II to State I was showed a signiﬁcantly lower in NSF patients. SF patients had compensatory enhancement of DFNC strengths between default and dorsal attention network, as well as within the default network. While reduced DFNC strengths of within-network and inter-network were both observed in NSF patients. Patients with abnormally temporal properties and more extension DFNC strength alterations were less likely to receive seizure freedom. Conclusions: Our study indicates that DFNC could offer a better understanding of dynamic neural impairment mechanisms of drug-resistant TLE functional network, epileptic brain network reorganization and provide a additional preoperative evaluation support for surgical treatment of drug-resistant TLE.